1993
DOI: 10.1037/1064-1297.1.1-4.242
|View full text |Cite
|
Sign up to set email alerts
|

Naltrexone reduces self-injury and improves learning.

Abstract: A cross-over study of 24 Ss with self-injurious behavior (SIB) was conducted over a continuous 10-week period. Treatment with naltrexone (NTX) was provided for 3 weeks in a randomized, reversal design with different doses or placebo each week. Videotaped observations (20 hr/subject), neurological examinations, and ratings of adaptive and maladaptive behavior were collected. Treatment with 2 mg/kg NTX produced at least a 50% reduction in SIB in a significant (p < .01) number of Ss. The 1.0 mg/kg was less effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 67 publications
2
51
0
Order By: Relevance
“…elevated transitional probability for SIB). Based on procedures employed in our previous studies (Sandman et al, 1997; Sandman, Touchette, Lenjavi, Marion, & Chicz-DeMet, 2003; Sandman et al, 1993) each subject was administered one of three doses of naltrexone (NTX; 0.5, 1.0 or 2.0 mg/kg, QOD) on separate weeks. Each positive treatment week was separated by a week of placebo treatment.…”
Section: Methodsmentioning
confidence: 99%
“…elevated transitional probability for SIB). Based on procedures employed in our previous studies (Sandman et al, 1997; Sandman, Touchette, Lenjavi, Marion, & Chicz-DeMet, 2003; Sandman et al, 1993) each subject was administered one of three doses of naltrexone (NTX; 0.5, 1.0 or 2.0 mg/kg, QOD) on separate weeks. Each positive treatment week was separated by a week of placebo treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Equivocal evidence also currently exists for opioid antagonists, some studies showing better results on large doses and others on small doses (Sandman et al, 1993;Willemsen-Swinkells et al, 1995;Casner et al, 1996;Sandman et al, 2000). There is currently no evidence available to support use of anti-anxiety medication (King & Davanzo, 1996), psychostimulants or vitamins.…”
Section: The Evidence Basementioning
confidence: 91%
“…Several articles reviewed [Aman et al, 1989;Anderson et al, 1984;Handen et al, 1990;and Lewis et al, 1995] that fit the criteria for this section also included follow-up studies that will be reviewed consecutively. Sandman et al [1993] used a double-blind, placebo-control study to examine the effects of naltrexone on self-injury and learning in 24 persons diagnosed with developmental disabili-ties. The purpose of the study also was to address some of the inconsistencies the authors identified in previous studies.…”
Section: Medication Effects On Multiple Dependent Variablesmentioning
confidence: 99%